Research on Connectivity of Multi-Type Heterogeneous Wireless Networks - Jingyuan Guo; Tao Yang; Hui Feng; Bo Hu (Dianxin kexue)
For the large scale Ad Hoc network with single-type or multi-type users, the percolation-based connectivity problem was addressed. Firstly, from the Boolean model point of view, single-type and multi-type user network connectivity was analyzed. For the single-type users, the sufficient condition under which percolation was achieved in clustered networks was formulated under the disk model. For multi-type user network, under the Poisson distributed cognitive radio model, the necessary condition for network connectivity was analyzed. The existence of a communication link between two secondary users depends on not only the distance between them, the transmitting and receiving activities of nearby primary users, but also the neighboring user's type. Then from random connection model point of view, the product rule was introduced to decide which two users could be connected, thus delaying or accelerating the occurrence of percolation. Various simulations show that the percolation is effective both in theory and practice in guidance of the deployment of cognitive radio network.